2020
DOI: 10.1111/eje.12618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the DC/TMD instructional video on the practical skills of undergraduate students—A single‐blinded, randomized controlled trial

Abstract: Introduction Competencies in the clinical examination of patients with temporomandibular disorders (TMD) can be achieved by self‐instruction. This study aimed to identify the impact of the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) instructional video on the practical examination skills of undergraduate students. Materials and methods One week prior to completing an objective structured clinical examination (OSCE) addressing the examination of patients with TMD, undergraduate students in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The results suggest that the video presentation and the VDI are integral features in interactive multimedia for use in software application courses. According to Rauch, Roesner, Hahnel & Schierz (2020), video presentations have a tremendous effect on learners who are learning practical skills. This study also introduces empirical evidence from the learners' perspective on the effect of these new technologies.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that the video presentation and the VDI are integral features in interactive multimedia for use in software application courses. According to Rauch, Roesner, Hahnel & Schierz (2020), video presentations have a tremendous effect on learners who are learning practical skills. This study also introduces empirical evidence from the learners' perspective on the effect of these new technologies.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Animated content significantly enhances a person's ability to learn practical skills (Rauch, Roesner, Hahnel & Schierz, 2020). Multimedia content can be used to visualize and simplify complex content.…”
Section: Animationmentioning
confidence: 99%
“…The advantage of video-based learning has been demonstrated in previous studies. [23][24][25][26][27] During the whole training process, the video clip demonstrating the use of the dental operating microscope and the instrument removal procedure was uploaded online and was available for trainees to enhance the learning process.…”
Section: The Questionnairesmentioning
confidence: 99%
“…Enhancing video demonstrations with subtitles of the presenter's dialog, text bullet points and summary text pages was found to improve undergraduate students’ ability to retain theoretical knowledge but not practical performance 19 . A study using an enhanced video with images and picture‐in‐picture videos to instruct undergraduate students on practical examination skills concluded that watching the video was highly recommended by the students 20 …”
Section: Introductionmentioning
confidence: 99%
“…19 A study using an enhanced video with images and picture-in-picture videos to instruct undergraduate students on practical examination skills concluded that watching the video was highly recommended by the students. 20 In-video quizzes or quiz questions embedded directly within the video to increase the interactivity of its content and support formative assessment have been minimally explored in the literature despite the positive results of using quizzes as a formative assessment technique. [21][22][23][24][25] Thus, this quasi-experimental investigation aimed to study the impact on second-year dental students' acquisition of knowledge, practical skills, and perceptions of the utility of a series of instructional simulation videos with embedded quiz items designed to improve students' learning and engagement compared and in combination with live hands-on demonstrations before each simulation session.…”
Section: Introductionmentioning
confidence: 99%